Seasonal changes in the distributions of fish and zooplankton across the Barents Sea Polar Front - Einat Sandbank; Malin Daase; Paul E. Renaud; Sünnje L. Basedow; Maxime Geoffroy (PLoS ONE, 2026)
Oceanic fronts are often characterized by high primary productivity and increased localized levels of species diversity and biomass; this is due in part to the mixing of distinct water masses as well as the aggregation of organisms by ocean currents. How these interactions between the physical and chemical parameters of the Barents Sea Polar Front impact pelagic ecology are poorly understood, particularly across seasons. By combining findings from continuous acoustic and hydrographic recordings with discrete sampling, we measured how hydrographic changes associated with the Barents Sea Polar Front modify the spatial distribution and biomass of fish and zooplankton across three seasons (spring, winter, and summer). We found the influence of the Polar Front on the ecology of pelagic organisms to be highly dependent on season, with spring having the strongest correlation between hydrographic parameters and species distribution. The Front’s influence on zooplankton and fishes differed considerably, as zooplankton and fish biomass often peaked at opposing ends of our survey transects, and in spring resulted in a zooplankton refuge from grazing fishes. The importance of seasonal sea ice was evident, and both the spring ice melt and new winter ice were strongly correlated with species distribution and in spring also biodiversity. Abiotic variables, and in particular temperature, were found to be the strongest predictors of pelagic fish and macrozooplankton biomass in all seasons, although in winter a greater influence by biotic variables was observed. While oceanic fronts are traditionally considered hotspots of biodiversity, the strong seasonal changes in the structure of the Barents Sea Polar Front create everchanging conditions where high biodiversity and pelagic biomass do not persist year-round. Our findings highlight the importance of considering seasonality in management decisions, and the need for increased in-situ winter data collection.